Colorimetric Chemical Differentiation and Detection of Phosphorus in Eutrophic and High Particulate Waters: Advantages of a New Monitoring Approach - Felgentreu, Lisa; Nausch, Günther; Bitschofsky, Franziska; Nausch, Monika; Schulz-Bull, Detlef (Frontiers in Marine Science, 2018)
Phosphorus (P) is a key factor forcing eutrophication in limnic and marine systems, and all monitoring programs for water quality accordingly include P determinations. However, traditional monitoring does not allow an analysis of the different components involved in the P cycle taking place in the water column. Nonetheless, the implementation of measures addressing eutrophication requires a full understanding of the processes involved in the transformation and transport of P, in all its chemical forms. In this study, the P categories present in a river and its estuary in northern Germany, which discharge into the Baltic Sea, were characterized. Using the molybdenum blue method we found that the classification of P into the traditional fractions (DIP, DOP, POP) applied in the ocean cannot be applied to turbid waters such as rivers because interferences between the fractions seems to occur. Therefore a new nomenclature has been introduced. In addition to total phosphorus (TP) and dissolved molybdate-reactive phosphorus (DRP; previously referred to as inorganic phosphorus), dissolved non-molybdate-reactive phosphorus (DNP), particulate molybdatereactive phosphorus (PRP), and particulate non-molybdate-reactive phosphorus (PNP) were distinguished. The high spatial and temporal variations in the proportions of these forms with respect to the TP concentration well demonstrate the complexity of the P cycle and the involved P fractions and emphasize the need for expanded monitoring approach. The potential of eutrophication could be underestimated if not all P categories were considered. With the new operational nomenclature the common and standardized molybdenum blue reaction could be used to implement the analysis of various P components into regular monitoring programs.